2021
DOI: 10.48550/arxiv.2106.06200
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Towards User-Driven Neural Machine Translation

Abstract: A good translation should not only translate the original content semantically, but also incarnate personal traits of the original text. For a real-world neural machine translation (NMT) system, these user traits (e.g., topic preference, stylistic characteristics and expression habits) can be preserved in user behavior (e.g., historical inputs). However, current NMT systems marginally consider the user behavior due to: 1) the difficulty of modeling user portraits in zero-shot scenarios, and 2) the lack of user… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 27 publications
0
1
0
Order By: Relevance
“…While human translation (HT) ensures quality translation, it is costly and time consuming (Zhou and Bollegala, 2019). However, recent advances by neural machine translation (NMT) (Vaswani et al, 2013;Luong, Pham, and Manning, 2015;Lin et al, 2021) have shown impressive results. In addition, NMT survey studies by Wang et al (2021) and Ranathunga et al (2021) suggest that though there is the scope of improvements in NMT systems, development of tools and resources for low-resourced languages (LRLs) (Koehn and Knowles, 2017) have greatly improved.…”
Section: Introductionmentioning
confidence: 99%
“…While human translation (HT) ensures quality translation, it is costly and time consuming (Zhou and Bollegala, 2019). However, recent advances by neural machine translation (NMT) (Vaswani et al, 2013;Luong, Pham, and Manning, 2015;Lin et al, 2021) have shown impressive results. In addition, NMT survey studies by Wang et al (2021) and Ranathunga et al (2021) suggest that though there is the scope of improvements in NMT systems, development of tools and resources for low-resourced languages (LRLs) (Koehn and Knowles, 2017) have greatly improved.…”
Section: Introductionmentioning
confidence: 99%